Numerical study on the mechanism of fluid energy transfer in an axial flow pump impeller under the rotating coordinate system - Guo, Yanlei; Yang, Congxin; Mo, Yingxiang; Wang, Yan; Lv, Tianzhi; Zhao, Sen (Frontiers in Energy Research, 2023)
Obtaining the fluid movement law and energy transfer and loss mechanism in the impeller of the axial pump is a necessary condition to improve the efficiency of the axial pump. Based on the shear stress transport k-ω turbulence model, a three-dimensional unsteady numerical simulation of the whole flow field of an axial flow pump was presented at different flow rates. Combined with the Bernoulli equation of relative motion, the flow field structure in the impeller under design condition was studied quantitatively in the rotating coordinate system. The fluid movement law and energy transfer and loss mechanism in the impeller of the axial flow pump were described in detail. This research has certain reference significance for further understanding the flow field structure in the impeller of the axial flow pump, improving its design theory and method, and then realizing its efficient and accurate design of the axial flow pump.